SAT0202 Short-term erosive progression on magnetic resonance images is highly correlated with long-term radiographic progression in rheumatoid arthritis wrists. (1st June 2001) - Østergaard, M; Hansen, M; Stoltenberg, M; Jensen, KE; Szkudlarek, M; Klarlund, M; Gideon, P; Pedersen-Zbinden, B; Lorenzen, I
Abstract : Background: Objectives: In patients with rheumatoid arthritis (RA) to compare the development of wrist joint bone erosions on conventional radiography (CR) performed annually for 5 years with erosions detected by magnetic resonance imaging (MRI) at baseline and 1-year follow-up. Methods: Fifteen patients with RA (disease duration 0.5–20 years, median 1.5 years) were followed for 5 years. MRI of the dominant wrist was performed at year 0 and 1, and CR at years 0, 1, 2, 3, 4 and 5. In each image set, the number of wrist bones (metacarpal bases, carpal bones, radius and ulna) with erosions was determined. Results: The number of bones with erosions detected by CR and MRI at the different time points are shown in the Table 1 . The total number of CR-erosions at baseline and after 5 years, compared with the number of MRI-erosions at baseline, were 21% and 64%, respectively. The MRI-erosion score at 1 year was the parameter from the initial 1 year of follow-up, that showed the closest statistical correlation with the radiographic erosion score at 5 years (rho = 0.67, p = 0.006), while corresponding correlations for radiographic erosion scores at baseline and 1 year were rho = 0.41 (p = 0.12, NS) and rho = 0.60 (p = 0.02). The erosive progression rate on radiographs during the 5 years (CR 5 minus CR 0) was significantly correlated with the MRI erosive progression rate during the initial year (MRI 1 minus MRI 0) (rho = 0.64, p = 0.01), and, more weakly, with the corresponding 1-year radiographic progression rate (rho = 0.56, p = 0.03). Conclusion: In the present study, short-term (1-year) MRI progression was highly significantly correlated with long-term (5 year) erosive progression. The study suggests that MRI is more useful than radiography itself for prediction of long term radiographic joint damage in rheumatoid arthritis.